BRAF p.Val600Glu (V600E) mutation detection in thyroid fine needle aspiration cell block samples. Issue 5 (August 2015) - Leslie, Connull; Grieu-Iacopetta, Fabienne; Richter, Anna; Platten, Michael; Murray, Jack; Frost, Felicity A.; Amanuel, Benhur; Kumarasinghe, M. Priyanthi
<x xml:space="preserve">Abstract</x> Summary Assessing BRAF mutation status in thyroid fine needle aspiration (FNA) cytology samples by both immunohistochemistry (IHC) and molecular methods has been documented in recent literature. We aim to highlight issues relating to quality and quantity of cellular material and DNA extracted from cell block samples. BRAF mutation status was assessed by both molecular and IHC methods in cell block material from thyroid FNA samples over a range of diagnostic categories, and correlated with available follow-up resection specimens. Of 39 samples there were 14 cases with 'inconclusive' cytology (Bethesda diagnostic categories 3, 4 or 5) and 25 cases with malignant cytology. Follow-up information was available in 38 of 39 cases and resection material for comparison in 18 of 39 case. Detection of BRAF mutation in cell block samples by combined molecular and IHC methods showed 100% specificity and 71.4% sensitivity compared to subsequent histologically confirmed BRAF mutated papillary thyroid carcinoma. IHC detected BRAF mutation in two (8.2%) cases which were negative by molecular methods and confirmed mutation positive by IHC and molecular methods on subsequent histology. Low extracted DNA concentration did not appear to preclude detection of BRAF mutation, although cell blocks with lower tumour cell content were over-represented in cases that were wild-type on FNA material and BRAF mutant on subsequent histology. BRAF mutation detection in cell block material is feasible and highly specific for papillary thyroid carcinoma. Best results are obtained by a combination of molecular and IHC methods.